Fostering the effectiveness of reportable arrangements provisions by enhancing digitalisation at the South African Revenue Service - Oguttu, Annet Wanyana (University of Pretoria, 2021)
Mini Dissertation (MPhil (International Taxation))--University of Pretoria, 2020.